2003
DOI: 10.1111/1464-0597.00123
|View full text |Cite
|
Sign up to set email alerts
|

Future Interaction Expectation and the Use of Soft and Hard Influence Tactics

Abstract: Les stratégies d'influence varient en fonction du contrôle qu'elles exercent sur la situation et la cible. Les stratégies "douces" laissent plus que les stratégies "dures" la possibilitié pour la cible d'accepter ou de rejeter la tentative d'influence. La solution "dure" engendre donc généralement une plus grande tension dans la relation entre la cible et l'agent d'influence. Cette recherche est centrée sur la conséquence que la représentation de l'interaction à venir peut avoir sur le choix d l'une ou l'autre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 47 publications
2
62
0
Order By: Relevance
“…The significant constant-effect on the ANOVA (M ¼ À3.28; F(1,86) ¼ 106.70, p < 0.0001, h 2 ¼ 0.55), indicated that soft tactics were indeed employed more often than strong ones. This finding is congruent with the results of other studies (Rule, Bisanz, & Kohn, 1985;van Knippenberg & Steensma, 2003;van Knippenberg, van Eijbergen et al, 1999;Yukl, Guinan, & Sottolano, 1995). An ANOVA on the frequency of coercion variable revealed the expected main effects of Competence (M ¼ 2.09; F(1,86) ¼ 4.26, p < 0.05, h 2 ¼ 0.05) and Reward Structure (F(2,86) ¼ 6.13, p < 0.005, h 2 ¼ 0.13).…”
Section: Frequency Of Coercionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significant constant-effect on the ANOVA (M ¼ À3.28; F(1,86) ¼ 106.70, p < 0.0001, h 2 ¼ 0.55), indicated that soft tactics were indeed employed more often than strong ones. This finding is congruent with the results of other studies (Rule, Bisanz, & Kohn, 1985;van Knippenberg & Steensma, 2003;van Knippenberg, van Eijbergen et al, 1999;Yukl, Guinan, & Sottolano, 1995). An ANOVA on the frequency of coercion variable revealed the expected main effects of Competence (M ¼ 2.09; F(1,86) ¼ 4.26, p < 0.05, h 2 ¼ 0.05) and Reward Structure (F(2,86) ¼ 6.13, p < 0.005, h 2 ¼ 0.13).…”
Section: Frequency Of Coercionsupporting
confidence: 90%
“…If this option was chosen the other person's initial answer would be replaced by the answer forced upon him or her by the participant. Thus, as in other studies on power and the use of hard versus soft tactics, participants could either force or advise the other person (Bruins et al, 1999;de Gilder & Wilke, 1994;van Knippenberg, van Eijbergen et al, 1999;van Knippenberg et al, 2001;van Knippenberg & Steensma, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…As such, hard tactics may occasionally enhance performance, but could also lead to demotivation and resistance (Van Knippenberg & Steensma, 2003), which has been associated with negative organizational outcomes (Kirkman & Shapiro, 1997).…”
Section: Hypothesis 1: Managers' Influence Tactic Ambidexterity Will mentioning
confidence: 99%
“…Despite the traditional interest on the nature and consequences of different types of influence behavior (e.g., Van Knippenberg & Steensma, 2003), very few studies have 27 differentiated between higher-order constructs of influence tactics, based on their relative position in the strength dimension (e.g., Sparrowe et al, 2006;Van Knippenberg et al, 1999a). Specifically, by examining the variation that soft and hard influence tactics exhibit on task performance we aim to broaden our understanding of the effectiveness of specific influence tactics.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…This behaviour is activated in a situation when a person of high DEI, having conducted a rational analysis, claims that the infl uence in a given situation is due to somebody else (an individual or group) and that their own infl uence is ineffective or unacceptable, or that the 'repertoire' of available infl uence tactics has been depleted. Van [55][56][57][58][59][60][61][62][63][64][65][66][67], as a result of the conducted research, stated that if partners expect to stay in the interaction in the future, they employ less severe infl uence means and generally try to have less infl uence on each other. Therefore, we presuppose that persons of high DEI consider a long-term prospect for common and effective functioning, reducing their own infl uence in a team, whereas in case of assumed short-term relations, more severe infl uence means may be anticipated.…”
Section: Conditions For Team's Cooperation In the Context Of Relationmentioning
confidence: 99%